Live Staphylococcus aureus Induces Expression and Release of Vascular Endothelial Growth Factor in Terminally Differentiated Mouse Mast Cells - Johnzon, Carl-Fredrik; Rönnberg, Elin; Guss, Bengt; Pejler, Gunnar (Frontiers in Immunology, 2016)
Mast cells have been shown to express vascular endothelial growth factor (VEGF), thereby implicating mast cells in pro-angiogenic processes. However, the mechanism of VEGF induction in mast cells and the possible expression of VEGF in fully mature mast cells have not been extensively studied. Here we report that terminally differentiated peritoneal cell-derived mast cells can be induced to express VEGF in response to challenge with Staphylococcus aureus, thus identifying a mast cell-bacteria axis as a novel mechanism leading to VEGF release. Whereas live bacteria produced a robust up-regulation of VEGF in mast cells, heat-inactivated bacteria failed to do so, and bacteria-conditioned media did not induce VEGF expression. The induction of VEGF was not critically dependent on direct cell-cell contact between bacteria and mast cells. Hence, these findings suggest that VEGF can be induced by soluble factors released during the co-culture conditions. Neither of a panel of bacterial cell-wall products known to activate toll-like receptor (TLR) signaling promoted VEGF expression in mast cells. In agreement with the latter, VEGF induction occurred independently of Myd88, an adaptor molecule that mediates the downstream events following TLR engagement. The VEGF induction was insensitive to Nuclear factor of activated T-cells (NFAT) inhibition but was partly dependent on the Nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) signaling pathway. Together, these findings identify bacterial challenge as a novel mechanism by which VEGF is induced in mast cells.